Mapping the Excited‐State Potential Energy Surface of a Photomolecular Motor. (27th April 2018) - Hall, Christopher R.; Browne, Wesley R.; Feringa, Ben L.; Meech, Stephen R.
Abstract: A detailed understanding of the operation and efficiency of unidirectional photomolecular rotary motors is essential for their effective exploitation in molecular nanomachines. Unidirectional motion relies on light‐driven conversion from a stable (1 a ) to a metastable (1 b ) conformation, which then relaxes through a thermally driven helix inversion in the ground state. The excited‐state surface has thus far only been experimentally characterised for 1 a . Here we probe the metastable, 1 b, excited state, utilising ultrafast transient absorption and femtosecond stimulated Raman spectroscopy. These reveal that the "dark" excited‐state intermediate between 1 a and 1 b has a different lifetime and structure depending on the initial ground‐state conformation excited. This suggests that the reaction coordinate connecting 1 a to 1 b differs to that for the reverse photochemical process. The result is contrasted with earlier calculations. Abstract : Starten des Motors : Struktur und Dynamik des angeregten Zustands in einem lichtgesteuerten, unidirektionalen, rotierenden Motor hängen von der Anfangsgeometrie ab. Ein detailliertes Verständnis der Arbeitsweise und Effizienz dieser Motoren ist notwendig, um sie effektiv in molekularen Nanomaschinen einsetzen zu können.